A Pilot Outreach HIV Testing Project Among Homeless Adults - Pichon, Latrice C.; Rossi, Kristen Rae; Chapple-McGruder, Theresa; Krull, Lisa Jane; Kmet, Jennifer; Carswell, April L. (Frontiers in Public Health, 2021)
Background. The Memphis metropolitan statistical area (MSA) represents a Deep Southern U.S. city disproportionally affected by the ongoing transmission of new HIV cases as well as those diagnosed in late-stage disease. This region is a subset of 9 states, including Memphis, Tennessee (project site), driving the epidemic in the United States. Memphis ranks 4th among all U.S. MSAs for new HIV infections and has been identified in the CDC’s Ending the HIV Epidemic Initiative as a high HIV burden geographic focus area. The Memphis Ryan White Part A Program conducted a pilot project among adults seeking services in Memphis emergency and transitional housing shelters to offer on-site, rapid HIV testing. In this paper we describe the results from this aforementioned pilot study, including the rate of HIV test acceptance and potential factors associated with a history of HIV testing in Memphis. Methods. Community-engaged research approaches were employed via a partnership between the local health department, a federally qualified faith-based health center, and an academic university. An interviewer-administered survey to measure potential factors associated with HIV testing history and voluntary HIV testing services were offered to adults living in transitional housing establishments. Bivariate chi-square analyses were performed to determine the association between predisposing, enabling, and need variables with HIV testing history in the past 12 months. Results. Survey respondents (n=109) were mostly cisgender male (n=96; 88.1%), African American (n=79; 72.5%) and reported engaging in condomless sex in the past 12 months (n=55; 50.5%). Acceptability and uptake of HIV testing was high (n=97; 89.0%). Conclusions. Implementing rapid HIV testing programs outside of traditional health care settings is a strategy that can be used to engage high-risk individuals and those unaware of their HIV status to get tested. To our knowledge, this study represents the first that documents HIV testing acceptance rates offered outside of traditional health care settings for homeless and transitionally housed adults in a Deep Southern state.